2018
DOI: 10.1111/cup.13104
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis: Histopathologic findings of parakeratosis and dermal edema revisited

Abstract: The cutaneous manifestations of dermatomyositis range from classical in the case of heliotrope rash and Gottron papules to less common papulosquamous and edematous/vesiculobullous lesions; histopathologic descriptions are dominated by interface dermatitis. We present a case of dermatomyositis with a combination of common and rare skin findings, both clinically and histologically. Increased awareness of papulosquamous and edematous lesions of dermatomyositis can help direct patient care. Although uncommon, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…The vesiculo-bullous lesions are attributable to edema in the upper dermis and (occasionally significant) mucin deposits [6]. It has been reported that patients with vesiculo-bullous DM have a less favorable prognosis and a higher incidence of malignancy, which may be associated with greater morbidity and mortality [3,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vesiculo-bullous lesions are attributable to edema in the upper dermis and (occasionally significant) mucin deposits [6]. It has been reported that patients with vesiculo-bullous DM have a less favorable prognosis and a higher incidence of malignancy, which may be associated with greater morbidity and mortality [3,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our patient exhibited unusually rare cutaneous manifestations consistent with vesiculo-bullous/erythemato-edematous DM. First described by Findlay in 1951, this disease variant has recently emerged as a paraneoplastic phenomenon [3,6]. Clinically, it may present with small vesicles and erosions or with large blisters.…”
Section: Discussionmentioning
confidence: 99%
“…Die beschriebenen Hautveränderungen zeigen zum einen charakteristische Zeichen einer DM wie Erytheme im Nacken (shawl sign), im Dekolleté (V-sign), an den Hüften (holster sign), scheckige Hyperpigmentierung (Poikilodermie) und ein zentrofaziales Erythem, während andere typische Hauterscheinungen wie der weinerliche Gesichtsausdruck durch ein charakteristisches fliederfarbenes, periorbitales Ödem (heliotropes Erythem) und erythematöse, lichenoide, konfluierende Papeln über den Metacarpophalangeal-und Interphalangealgelenken (Gottron-Papeln) fehlen [2,5]. Zudem weist der Patient ungewöhnlich seltene Hauterscheinungen einer vesikulobullösen oder erythroödematösen DM auf, die 1951 von Findlay das erste Mal beschrieben wurde und gegenwärtig zunehmend als paraneoplastisches Phänomen diskutiert wird [3,6]. Diese vesikulobullöse Form kann auftreten in Form von kleineren Vesikeln und Erosionen, aber auch in Form von großen Bullae und findet sich oftmals am Stamm, den Extremitäten und im Gesicht [7][8][9], ähnlich wie bei unserem Patienten.…”
Section: Aufgrund Derunclassified
“…Die vesikulobullösen Läsionen kommen durch ein Ödem in der oberen Dermis mit zum Teil reichlichen Muzinablagerungen zustande [6]. In der Literatur wird eine schlechtere Prognose und eine höhere Malignominzidenz bei Patienten mit vesikulobullösen Formen der DM beschrieben, welche mit einer höheren Morbidität und Mortalität einhergehen kann [3,[9][10][11].…”
unclassified